HISTORY OF FORMATION AND DEVELOPMENT OF FUNCTIONS OF THE STATE IN THE FIELD OF PROTECTION OF THE POPULATION AND TERRITORIES FROM EMERGENCY SITUATIONS - Shoyko , Vasyl (Theory and Practice of Public Administration, 2020)
The article substantiates that in the history of the formation and development of the functions of the state in the field of protection of the population and territories from emergency situations there is a period that needs to be specified, substantially supplemented and enriched with known historical facts. This period, which did not receive the attention of scientists, covers the development of the field of public security management from ancient times, to the beginning of the twentieth century.It is determined that, in the general case, the topic of the beginning of the emergence and sustainable development of fire safety measures has received much more interest of scientists than the historical theme of the establishment of public administration mechanisms in the field of protection of the population and territories from the consequences of emergencies, in general. It is proved that, to date, there is no consensus on the classification of the stages of their evolution in the relevant time frames. However, almost all scholars in the field of government emphasize that the changes that have taken place in the global military and political arena have a direct impact on this process. In particular, it concerns changes in the ways of conducting armed combat and the emergence of modern means of destruction and variants of their combat use.There are three main stages of the development of mechanisms of public administration in the field of civil protection: the first stage (X century BC - XVIII century AD), the second stage (XVIII century - 30 years of XX century). and the third stage (1930’s - our time).